Women in the Law School Curriculum: Equity is About More Than Just Access - Rachael Field (Legal Education Review)
[Extract] As students have become increasingly familiar with, and dependent on, computer technology, the boundaries of what constitutes a comfortable, stimulating, flexible and varied learning environment have altered. This inevitably adds to the demands placed on those individuals who have painstakingly developed, programmed, tested, and refined unique computer packages for student learning. Keeping materials updated is of particular importance in legal education, and this maintenance function alone can consume substantial resources. The task of adapting an existing program to incorporate textual changes and new technologies on an ongoing basis, while concurrently developing new programs, is a particularly overwhelming one. Indeed, the task may be beyond individuals or even institutions. For the program author who wishes to capitalise on work already completed and to enhance the benefits gained thereby, a different approach to future development is clearly required.